EFFECT OF GIVING DIFFERENT DOSES OF VITERNA SUPLEMENT WITH ARTIFICAL FEED ON THE GROWTH DAN SURVIVAL OF CATFISH (Ompok hypopthalmus) WITH A RECIRCULATION SYSTEM - Dita Lorenza; Niken Ayu Pamungkas; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The purpose of this research was to study the effect of giving different doses of viterna suplement with artifical feed on the growth dan survival of catfish (ompok hypopthalmus) with a recirculation system. The method used was the experimental method, namely a completely randomized design (CRD) of one factor with 5 levels of training and 3 replications required 15 experimental units with training P0 (without viterna), P1 (viterna 13 ml/kg of feed) , P2 (viterna 15 ml/kg of feed), P3 (viterna 17 ml/kg of feed), P4 (viterna 19 ml/kg of feed). The results of the research was absolute weight growth, absolute length growth, increased fish growth, daily growth rate, survival rate, and feed conversion ratio (FCR) the best in P3 with the use of viterna 17 ml/kg of feed. Keywords: viterna plus, Catfish, recirculation system, survival rate.